2007
DOI: 10.1002/app.25305
|View full text |Cite
|
Sign up to set email alerts
|

Plasma surface modification and characterization of collagen‐based artificial cornea for enhanced epithelialization

Abstract: Argon plasma treatment enhanced the attachment of epithelial cells to a collagen-based artificial cornea crosslinked using glutaraldehyde (GA) and glutaraldehyde-polyethylene oxide dialdehyde (GA-PEODA) systems. The epithelialization of untreated and treated surfaces was evaluated by the seeding and growth of human corneal epithelial cells. Characterization of polymer surface properties such as surface hydrophilicity and roughness was also made by contact angle measurement and atomic force microscopy, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…These active species in argon plasmas can react with the treated surface and thus modify the surface chemistry and properties without affecting the bulk material properties . It has been reported that, after treatment with argon plasma, the water contact angle of the collagen surface is significantly decreased . The dentin surface contains a fibrous collagen network, after removal of drilling debris and some surface minerals by acid etching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These active species in argon plasmas can react with the treated surface and thus modify the surface chemistry and properties without affecting the bulk material properties . It has been reported that, after treatment with argon plasma, the water contact angle of the collagen surface is significantly decreased . The dentin surface contains a fibrous collagen network, after removal of drilling debris and some surface minerals by acid etching.…”
Section: Discussionmentioning
confidence: 99%
“…The bonding strength of specimens with an interface area of 1 mm 2 ranged from 40 to 60 MPa. When the interface area was increased to 2 mm 2 , the bonding strength decreased to [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] MPa. This is probably a result of the presence of a greater number of defects in specimens with a large bonding surface area (10).…”
mentioning
confidence: 99%
“…The examples of the former are modified and unmodified copolymers of 2-hydroxyethyl methacrylate (HEMA) and methyl methacrylate (MMA) [ 2 ]. Natural polymers used for the fabrication of scaffolds include gelatin and chondroitin sulfate [ 17 ], silk fibroin [ 18 ], recombinant human collagen [ 19 ], and argon plasma treated collagen [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noble gases-based plasma treatment has widely been used in a diversity of applications, e.g., surface modification of polymers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], glass [ 18 ], carbon fibres [ 19 ], superconductors [ 20 ], metal and alloys [ 21 , 22 ], and textiles [ 23 , 24 , 25 , 26 ]. As for medical uses, there are several studies conducted on cleaning surfaces [ 27 , 28 , 29 ] and cell attachment [ 30 , 31 , 32 , 33 , 34 , 35 ]. In this contribution, focus is directed onto the surface modification via argon plasma treatment and examination of keratinocyte human cell growth on atelocollagen surfaces which has not yet been done.…”
Section: Introductionmentioning
confidence: 99%